Development of Surrogate in Vitro Systems to Model MDS and AML Human Diseases - Ronconi, Michela (My University, 2024)
Myelodysplastic Syndromes (MDS) represent a pre-malignant myelopoiesis originating from hematopoietic stem and progenitor cells (HSPCs) that results in inefficient hematopoiesis and cytopenia. In one case out of three, MDS progress to lethal secondary acute myeloid leukemia (sAML) that manifests a block in differentiation and immature leukemic blasts accumulation, with patients presenting a poor 5-year survival rate <20%. Although the genetic landscapes of human MDS and AML have been examined, the heterogeneity of the diseases, together with the scarcity of available models, has prevented a clear understanding of the molecular mechanisms behind the onset and progression of the disease. Here, we describe the development and optimization of two potential surrogate in vitro systems that have been initiated in our lab in an effort to overcome the principal limitations of existing models, while expanding on our current knowledge of MDS and AML biology. Specifically, building on an in vivo murine model of MDS to AML transition we previously established in our lab, we developed an inducible in vitro system that mimics MDS and AML features by genetic deletion of Gsk3α and Gskβ used in the in vivo HSC transplant system previously. This in vitro model allows for the expansion of diseased HSPCs, providing the opportunity of directly studying the disease initiating cells in a reproducible manner as they transition to AML in the absence of the in vivo requirements that limit analysis. The robustness of this model allowed us to capture epigenetic aberrations leading to MDS onset and its progression to AML. In a secondary in vitro model, we have taken advantage of our recently optimized techniques to reprogram primary AML cells from patients into induced pluripotent stem cells (iPSCs). AML pluripotent reprogramming provides a robust in vitro system that several patient lines. This model allows for clone-specific analysis recapitulating aspects of the genetic heterogeneity observed in AML disease. Upon adaptation of these lines to self-renewing culture system in the absence of co-culture, we were able to better perform hematopoietic differentiation using a subset of these patient derived iPSCs lines and demonstrate that iPSCs lines harboring AML patient-specific genetic mutations present a blocked differentiation, whereas iPSC lines devoid of somatic aberrations display normal hematopoiesis. The initial characterization of both surrogate systems provides potential unique aspects for study that would not have been captured using bulk samples due to the heterogeneity and inability to sustain primary patient derived cells in vitro. Furthermore, these systems may be compatible with high-throughput analysis and hold promise as a valuable tool for small molecule screening in the future.